Pharaoh Cuttlefish, Sepia pharaonis, Genome Reveals Unique Reflectin Camouflage Gene Set - Song, Weiwei; Li, Ronghua; Zhao, Yun; Migaud, Herve; Wang, Chunlin; Bekaert, Michaël (Frontiers in Marine Science, 2021)
Sepia pharaonis, the pharaoh cuttlefish, is a commercially valuable cuttlefish species across the southeast coast of China and an important marine resource for the world fisheries. Research efforts to develop linkage mapping, or marker-assisted selection have been hampered by the absence of a high-quality reference genome. To address this need, we produced a hybrid reference genome of S. pharaonis using a long-read platform (Oxford Nanopore Technologies PromethION) to assemble the genome and short-read, high quality technology (Illumina HiSeq X Ten) to correct for sequencing errors. The genome was assembled into 5,642 scaffolds with a total length of 4.79 Gb and a scaffold N50 of 1.93 Mb. Annotation of the S. pharaonis genome assembly identified a total of 51,541 genes, including 12 copies of the reflectin gene, that enable cuttlefish to control their body coloration. This new reference genome for S. pharaonis provides an essential resource for future studies into the biology, domestication and selective breeding of the species.